Separación de compuestos del bio-oil según su peso molecular y polaridad para la obtención de fracciones homogéneas - Sabina Delgado, Arianna; Pequerul Sariñena, Jorge; Fonts, Isabel; Gil-Lalaguna, Noemí; Sánchez, José Luis (Jornada de Jóvenes Investigadores del I3A, 2023)
This work is part of a project whose objective is to develop a fractionation method to separate the bio-oil produced in the pyrolysis of biomass into more homogeneous fractions with respect to molecular size and polarity. For this purpose, Liquid Flash Chromatography and Thin Layer Chromatography techniques applied to phenolic compounds usually present in bio-oil have been used.